Comparative genomic and virulence analyses of a novel sequence type 420 Streptococcus equi subspecies zooepidemicus isolated from donkey - Yuhui Tian; Yan Su; Xinyu Jiang; Lingling Su; Baojiang Zhang; Fenfen Lv (Virulence)
The zoonotic pathogen Streptococcus equi subspecies zooepidemicus (SEZ) frequently colonizes equines harmlessly but can occasionally cause disease or cross species barriers. Currently, growing evidence suggests SEZ can lead to severe clinical manifestations in horses and other animals, posing a threat to human and companion animal health. In this study, we sequenced the complete genome of the SEZ strain HT321, a novel sequence type 420 isolated from a donkey with a respiratory infection in China. Subsequently, we conducted comparative genomics, core genome single nucleotide polymorphisms (cgSNP), phylogenetic analysis multilocus sequence typing (MLST), and in vitro pathogenic analysis of this isolate. 118 genes in HT321 were annotated as antibiotic resistance genes (ARGs) and comparative genomics revealed that HT321 contained more lincosamide ARGs compared to other strains. The genomic island of HT321 carried more defensive virulence genes than that in the horse strain JMC111. Furthermore, compared to the reference equine strain JMC111, HT321 exhibited superior antimicrobial resistance and biofilm formation capability but lower pathogenicity. Interestingly, core genome single-nucleotide polymorphism phylogenetic analysis of 51 SEZ strains demonstrated that HT321 clustered with horse and donkey SEZ strains as well as S. canis strains. Notably, MLST analysis of the HT321 and 116 SEZ strains indicated that the HT321 donkey strain was related to SEZ canis isolates. These findings provide valuable insights for understanding, tracking, controlling, and preventing diseases caused by SEZ in donkeys.